2018
DOI: 10.1088/1538-3873/aae961
|View full text |Cite
|
Sign up to set email alerts
|

Carnegie Supernova Project-II: The Near-infrared Spectroscopy Program

Abstract: Corresponding author: E. Y. Hsiao ehsiao@fsu.edu * This paper includes data gathered with the 6.5-m Magellan telescopes at Las Campanas Observatory, Chile. Hsiao et al.Shifting the focus of Type Ia supernova (SN Ia) cosmology to the near-infrared (NIR) is a promising way to significantly reduce the systematic errors, as the strategy minimizes our reliance on the empirical width-luminosity relation and uncertain dust laws. Observations in the NIR are also crucial for our understanding of the origins and evoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 122 publications
1
64
0
Order By: Relevance
“…A telluric correction was applied to the IMACS and FLOYDS spectra following the method used for the EFOSC2 spectra. Two NIR spectra were obtained with Magellan+FIRE (Simcoe et al 2013) and were reduced following the method described in Hsiao et al (2019) using the tailored pipeline firehose (Simcoe et al 2013). An absolute flux calibration was applied using coeval photometric data.…”
Section: Optical and Nir Spectroscopymentioning
confidence: 99%
“…A telluric correction was applied to the IMACS and FLOYDS spectra following the method used for the EFOSC2 spectra. Two NIR spectra were obtained with Magellan+FIRE (Simcoe et al 2013) and were reduced following the method described in Hsiao et al (2019) using the tailored pipeline firehose (Simcoe et al 2013). An absolute flux calibration was applied using coeval photometric data.…”
Section: Optical and Nir Spectroscopymentioning
confidence: 99%
“…This was followed by a second SweetSpot data release, which included a total of 33 SN Ia with 168 JHK s observations in the redshift range 0.02 < z < 0.09, well into the smooth Hubble flow, but which did not yet include NIR Hubble diagrams (Weyant et al 2018 Krisciunas et al 2017), was recently analyzed in Burns et al (2018), which found peculiar velocity corrected Hubble diagram dispersions of ∼ 0.08 − 0.15 mag, depending on the subset of the 120 SN Ia they considered. Additional CSP-II photometric data, to be published in 2019, was recently described in Phillips et al 2019. Hsiao et al (2019 present an overview of the NIR SN Ia spectroscopy obtained by the CSP and the Center for Astrophysics (CfA) Supernova Group.…”
Section: Sn Ia In Nir As Standard Candlesmentioning
confidence: 99%
“…Gemini/GNIRS data were taken in cross-dispersed mode with the 0 675 slit, yielding continuous wavelength coverage from 0.8 to 2.5 μm and an R∼1000. These data were reduced with the XDGNIRS pipeline provided by Gemini Observatory, as described in Sand et al (2016) and Hsiao et al (2019).…”
Section: B2 Nir Spectroscopymentioning
confidence: 99%
“…IRTF spectra were taken in SXD mode and the 0 5 slit, yielding wavelength coverage from ∼0.8 to 2.4 μm and R∼1200. These data were reduced using the publicly available Spextool software package (Cushing et al 2004), as described in Hsiao et al (2019).…”
Section: B2 Nir Spectroscopymentioning
confidence: 99%